Early Clinical Predictors of Neurological Outcome in Children With Asphyxial Out-of-Hospital Cardiac Arrest Treated With Therapeutic Hypothermia - Lin, Jainn-Jim; Lin, Ying-Jui; Hsia, Shao-Hsuan; Kuo, Hsuan-Chang; Wang, Huei-Shyong; Hsu, Mei-Hsin; Chiang, Ming-Chou; Lin, Chia-Ying; Lin, Kuang-Lin (Frontiers in Pediatrics, 2020)
Abstract Aim: The aim of the current study was to identify early clinical predictors of neurologic outcome in children with asphyxial out-of-hospital cardiac arrest (OHCA) treated with therapeutic hypothermia. Methods: The present retrospective cohort study of comatose children treated with therapeutic hypothermia or normothermia after asphyxial OHCA was conducted between January 2010 and June 2018. All children aged between 1 month and 18 years of age, with a history of at least 3 minutes of chest compressions were eligible for inclusion. Their 6-month neurological outcomes were evaluated using the Pediatric Cerebral Performance Category (PCPC) score and early clinical predictors were determined. Results A total of 100 patients met the eligibility criteria for the study. Sixty-four (64%) of the children were male, and the mean age of participants was 4.59±5.45 years. Forty (40%) of the children had underlying disorders. The overall 1-month survival rate was 36%. Only 12 (12%) of the patients had favourable outcomes (PCPC ≤2). Thirty-four (34%) of the 100 children were receiving therapeutic hypothermia. In the univariate analysis, an initial lactate level of ≤80 mg/dL, a Glasgow coma scale (GCS) score of 5-8, a GCS motor score ≥4 and a present pupil reflex before therapeutic hypothermia, were significantly associated with favourable 6-month neurological outcomes. However, after the multivariate logistic analysis, only initial serum lactate level and GCS before therapeutic hypothermia were significantly associated with favourable 6-month neurological outcomes. Conclusion Initial serum lactate level and GCS before therapeutic hypothermia were significantly associated with 6-month favourable neurological outcomes in paediatric asphyxial OHCA patients who were treated with therapeutic hypothermia. Therefore, these early clinical predictors could be helpful to facilitate future clinical research in children with asphyxial OHCA treated with therapeutic hypothermia.